Building 'a natural industry of this country': an environmental history of the Ontario cheese industry from the 1860s to the 1930s - Goodchild, Hayley (My University, 2017)
This dissertation examines the origins and development of the cheese industry in rural Ontario between the 1860s and 1930s from the perspective of environmental history. Scholars have generally accepted contemporary beliefs that cheese was a “natural industry of this country” and that its growth was cooperative and inevitable. This dissertation tests these claims by comparing the rhetoric and actions of the rural elite and state officials against the human and extra-human work involved in manufacturing cheese for export, a method that has yielded new interpretations about the character and development of the industry. I build on James Murton’s concept of “alternative rural modernity” to argue that rural cheese manufacturing was a project of rural reform encouraged by elite ‘dairy reformers,’ rather than a natural development. Reformers believed cheese factories could support the social, economic and environmental stability of rural society indefinitely. Through cheese, they sought to create a society that was liberal and capitalist, but also cooperative and stable. They also believed that dairying would restore fertility to the region’s soils. In practice, however, their results were mixed. Although cheese became one of the province’s most significant export-oriented industries, transformed the environment, and deepened liberal values amongst rural people, it failed to deliver the alternative rural modernity reformers had envisioned. I provide two reasons why. First, the reformers’ mechanistic vision could not contend with the complexity and unpredictability of the socio-ecological world they sought to control. Second, the industry could not withstand the pressures of the emerging global capitalist food system and, ironically, facilitated the rise of ‘Big Dairy’ after the First World War, which hastened the industry’s demise. Overall, this dissertation emphasizes the dynamism of rural Ontario, contributes to an environmental history of liberal order in Canada, and contextualizes the resurgence of craft-based rural development in the twenty-first century.
An environmental history of the Ontario cheese industry
Keywords: cheese industry; Ontario; environmental history; dairying; alternative rural modernity; work; rural history